2014
DOI: 10.1111/petr.12395
|View full text |Cite
|
Sign up to set email alerts
|

Results after the adoption of a MELD/PELD‐based liver allocation policy in Argentina

Abstract: In July 2005, Argentina switched from a categorical liver allocation system to a MELD/PELD-based policy for patients with CLD. To analyze WL outcomes and survival after LT in children. From January 2000 to December 2010, 923 children were registered. Two consecutive five-yr periods were analyzed and compared: Era I (January 2000-July 2005) (n = 379) and Era II (July 2005-December 31, 2010) (n = 544). All data were prospectively collected and analyzed using the Kaplan-Meier method. After adopting the MELD/PELD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 12 publications
1
10
0
2
Order By: Relevance
“…Analyzing the pre‐ and post‐PELD eras, there was a 44% increase in the waiting list, as well as the number of liver transplants performed increased by 24%. Waiting list mortality rates lowered from 32% to 18%, comparing pre‐ and post‐PELD eras . Also interesting was the change in the baseline disease that indicated the liver transplant over the last decade: The emergency etiology has abruptly lowered since the universal Hepatitis A vaccine was instituted in 2005 National organization websites do not provide survival data or waiting list mortality data .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyzing the pre‐ and post‐PELD eras, there was a 44% increase in the waiting list, as well as the number of liver transplants performed increased by 24%. Waiting list mortality rates lowered from 32% to 18%, comparing pre‐ and post‐PELD eras . Also interesting was the change in the baseline disease that indicated the liver transplant over the last decade: The emergency etiology has abruptly lowered since the universal Hepatitis A vaccine was instituted in 2005 National organization websites do not provide survival data or waiting list mortality data .…”
Section: Resultsmentioning
confidence: 99%
“…Seda-Neto et al showed, in a cohort of 430 Data from the World Health Organization (1) and IroDat (7). comparing pre-and post-PELD eras (17 (7), the deceased donor transplantation rate was only 3.71 pmp in 2013, not much different from previous years. This is in part secondary to the lack of federal funding for donation and transplantation activities and the fragmentation of the healthcare system.…”
Section: Brazilmentioning
confidence: 87%
“…For data analysis, two groups were compared: CLD patients with accepted PELD/MELD exceptions (exception PELD/MELD Group) compared to non‐exception CLD patients with a PELD/MELD score ≥19 points (PELD/MELD group). Dip et al showed that the cutpoint that best discriminated between alive and dead patients on the WL at 3 months in Argentina was a calculated PELD of 19 with a sensitivity of 83.2 and a specificity of 83.3. Primary outcomes were as follows: (i) liver transplant accessibility (transplants/listed patients), (ii) WL mortality (deaths/listed patients), (iii) total dropout (removals because of death + too sick/listed patients) and (iv) post‐transplant patient survival.…”
Section: Methodsmentioning
confidence: 99%
“…These scoring systems are based on an objective formula that accurately predicts the mortality of patients with CLD at 3, 6, 9, and 12 months . Using this allocation system, WL mortality has decreased significantly in adult and pediatric patients with CLD . There is now an increasing number of older, clinically severe adults on the WL for LT, which, coupled with a shortage of donors, leads to competition with the pediatric population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation